Patient-controlled epidural analgesia versus conventional epidural analgesia after total hip replacement - a randomized trial - Maca, Jan; Neiser, Jan; Grasslova, Lenka; Trlicova, Michaela; Streitova, Dana; Zoubkova, Renata (Biomedical papers, 2020)
Aims: Patient-controlled analgesia (PCA) is usually considered a better option for pain management compared to conventional analgesia. The beneficial effect of PCA has been assessed in a number of studies; however, the results are inconsistent. The goal of this study was to compare of patient-controlled epidural analgesia (PCEA) to conventional epidural analgesia after total hip replacement (THR). Methods: This prospective study was performed at the Department of Anesthesia and Intensive Care Medicine at a tertiary university hospital. After THR, patients were admitted to the intensive care unit (ICU) and randomized to one of two groups (PCEA and non-PCEA). Postoperative pain in the PCEA group was treated using a standardized protocol, while the analgesia in the non-PCEA group was based on physician prescription according to the patient's clinical condition. The total consumption of analgesics, patients' satisfaction, pain intensity, and analgesia-related complications were recorded for 24 h after surgery. Results: The final sample consisted of 111 patients (PCEA group, n=55 and non-PCEA group, n=56). The PCEA group had significantly lower total consumption of analgesic mixtures (0.9±0.3 and 1.3±0.4 mL/kg per day, P<0.001).There was greater patient satisfaction (P<0.001) in the PCEA group. The mean pain intensity over 24 hours postoperatively was similar for both groups (P=0.14). There was no significant difference in rate of analgesia-related complications between the groups (hypotension, P=0.14; bradypnea, P=0.11). Conclusion: Compared to conventional epidural analgesia based on physician prescription, PCEA led to less total analgesic consumption and greater patient satisfaction after THR.
Keywords: patient-controlled analgesia; epidural analgesia; analgesics; drug consumption; total hip replacement; pain relief